EL POTENCIAL HUMANO Y LOS ESTÍMULOS ORGANIZACIONALES - Tito Huamaní, Pedro Leonardo (2005)
The results of the present investigation reveal the strategies that should be used to motivate the worker average in assistance institutions of the Sector Health. These they are related with the satisfaction of training necessities, promotion and ascents, and institutional recognition to the developed work. This order revealed by the surveys applied the workers of the Perinatal Maternal Specialized Institute (IEMP), the bound stimuli to economic and pecuniary aspects occupy the third group of preferences after the improvement of labor conditions, via permanent equipment and appropriate materials for their work. Such results are inverse to that proposed by Abraham Maslow, in their famous theory of the hierarchy of necessities. The results also reveal that the workers of the Sector Health - via investigation in the IEMP - they demand a democratic institutional address that allows them to make decisions in inherent activities to their function and to contribute constructively in the institutional development. It implies a change of paradigms, of the directive and intermediate bosses who should learn how to trust and to delegate the functions in their collaborators.